Outcome of Continuous versus Interrupted Sutures for Circumcision (Medicine Today, 2025)
Introduction: Circumcision is the most common pediatric surgical procedure all over the world. Suturing techniques are of two ways and complications are minimum in both these procedure. But bleeding and infection are the major complications associated with interrupted sutured circumcision. Continuous sutures had better outcome and showed less wound dehiscence than interrupted sutures. Hence, continuous suturing techniques were explored to replace the interrupted absorbable sutures. This study was conducted to compare the outcome of continuous and interrupted absorbable suturing techniques. Materials and Methods: This prospective study was conducted at the department of pediatric surgery BIRDEM General Hospital and Khidma Hospital, Dhaka, Bangladesh, among 250 children undergoing circumcision between January 2023 and December 2023. Among them, 125 patients underwent circumcision with continuous absorbable suturing techniques (group I) and 125 patients with interrupted absorbable suturing technique (group II). Comparative outcome analysis of both the groups was done based upon the following parameters- bleeding, infection, surgical wound dehiscence, swelling in the penis, Visual Analog Score (VAS) for pain assessment and cosmesis. The comparison of quantitative variables between the groups was done using chi-square test. Results: The age was 6.4±1.3 years in group I and 5.8±1.4 years in group II. Religious region was the commonest indication for circumcision (72%). The average healing period was six days in group I and 8 days in group II. No major surgical complications were observed in both the groups. But fewer postoperative complications were encountered in group I with respect to group II. As wound infection (p-value=0.05) is more common in group II. Circumcision done in group I (very good: 90.4%) was cosmetically superior to the patients in group II (very good: 40.8%) in which sutured marks were usually observed (p